(untitled) (Advances in Military Technology, 2010)
The capability of frangible bullet to disintegrate hitting the surface of a hard target can be expressed according to the [1] by so called Frangibility Factor. At the time there are several procedures serving for evaluation of the frangibility of the frangible bullet. As far as it is known to me, all of these methods are experimental. This article deals with the theoretical criterion of the evaluation of the Frangibility Factor. This criterion is based on the evaluation of the static strength of frangible bullet and on the theoretical calculation of the limit kinetic energy of the bullet hitting the hard target of known mechanical properties.